2015
DOI: 10.1108/md-07-2013-0379
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of perceived organizational support on the relationship between emotional labor and job-related outcomes

Abstract: Purpose – The purpose of this paper is to attempt to investigate how emotional labor strategies (i.e. surface acting and deep acting) affect job performance through job satisfaction. Another important objective of this study was to see whether perceived organizational support (POS) moderates the relationship between emotional labor strategies and job-related outcomes (i.e. job satisfaction and job performance). Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
6
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 64 publications
(106 reference statements)
10
68
6
3
Order By: Relevance
“…It is not surprising that the present study disclosed the significant moderating effect of POS on the relationship between surface acting on the one hand and job satisfaction and organizational commitment on the other hand. This finding is consistent with other empirical studies conducted by Hur, Won Moon and Jun () as well as Hur et al (). Conversely, whereas the present study found a significant moderating effect of POS on the relationship between deep acting and organizational commitment, POS did not moderate the relationship between deep acting and job satisfaction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is not surprising that the present study disclosed the significant moderating effect of POS on the relationship between surface acting on the one hand and job satisfaction and organizational commitment on the other hand. This finding is consistent with other empirical studies conducted by Hur, Won Moon and Jun () as well as Hur et al (). Conversely, whereas the present study found a significant moderating effect of POS on the relationship between deep acting and organizational commitment, POS did not moderate the relationship between deep acting and job satisfaction.…”
Section: Discussionsupporting
confidence: 93%
“…This finding presupposes that employees' engagement in deep acting will have significant bearing on the level of employee commitment to their organization, and they fall on the level of their organization's support; when they see their organization to be more supporting, the more likely that acting in good faith will have consequences on their organizational commitment. This finding is also consistent with the empirical studies by Hur et al () as well as Han et al () who pointed to the moderating effect of POS in the relationship between deep acting and organizational commitment. The finding suggests that nurses and midwives seek support from their organization in the process of managing the emotional demands of the profession.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Jain et al (2013) suggested that employees' outputs are the direct function of the inputs that they receive from their organizations in any social exchange. In fact, the extent of employees' effort in the job is manifested by their feelings of endorsement given by the organizations, which in turn, enhances the level of engagement (Hur et al, 2015). The presence of higher level of organizational support can compensate relatively low level of job related resources that results in employees' positive attitudes as employees exert higher energy in investing extra effort in the workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Shantz et al (2014) found that POS moderates the relationship between employee engagement and turnover intentions and argued that employees show low level of intentions to leave the organization as POS has compensated the relatively low level of employee engagement. Similarly, Hur et al (2015) found the moderating role of POS on the link between employees' emotion and outcome variables among the service employees. With this line of reasoning, the present hypothesized the moderating role of POS on the relationship between HRM practices and employee engagement such that the effect of poor perceptions of employees regarding HRM practices can be compensated by POS on employee engagement.…”
Section: Moderating Role Of Perceived Organizational Supportmentioning
confidence: 99%